Understanding The Effect of Human Capital Management Practices, Psychological Capital, and Employee Engagement To Employee Performances - Witasari, Jessica; Gustomo, Aurik (School of Business and Management Institut Teknologi Bandung, 2020)
Abstract. As the main factor of creative business, creative and innovative employees are indispensable resources to respond to a dynamic business environment complexity nowadays in an adequate manner. Therefore, an entity should be more flexible and punctual during the talent acquirements process, especially in a creative industry like architecture. The realization upon the importance of human capital determines the business unit to concern with precise human capital management practices, employee engagement, and psychological capital as preventive solutions to improve employee performance. However, the study whereby these variables are connected remains insufficient. Accordingly, this study aims to discover: (1) the relation between human capital management practices, psychological capital, employee engagement, and employee performance; and (2) the direct and indirect impacts among the variables with their significance. A questionnaire used for data collection that furtherly analyzed utilizing structural equation modeling by SmartPLS to examine the relationship between the variables. Expected outcomes of this research contribute to people and management topics, notably in human capital management and creative industry literature. For practical contributions, this research provides credible proves of how engagement and psychological capital have an essential role to be implemented in architectural firms.Keywords: Employee engagement, employee performance, human capital, psychological capital, creative industry